Proliferation Index Predicts Survival after Second Craniotomy within 6 Months of Adjuvant Radiotherapy for High-grade Glioma. Issue 3 (March 2016) - Gzell, C.; Wheeler, H.; Huang, D.; Gaur, P.; Chen, J.; Kastelan, M.; Back, M.
Abstract: Aims: To determine pathological features that predict survival in patients having repeat craniotomy within 6 months of radiotherapy for high-grade glioma (HGG). Materials and methods: HGG patients (World Health Organization grade 3/4) managed with repeat craniotomy within 6 months of completing radiotherapy between 2008 and 2012 were included. Based on the presence of residual tumour cells, the pathology was reported as pathological progression or pathological pseudoprogression. The proliferation index (Ki67) was reported and compared with initial pathology as a percentage change. Tumour necrosis was estimated as a percentage of the specimen. Overall survival was calculated in months. Results: Of 327 patients managed with HGG, 27 patients underwent repeat craniotomy within 6 months of radiotherapy. The median survival after reoperation was 11 months (95% confidence interval 1–22). Ki67 at reoperation of 0%, 1–9% and >10% was associated with survival with a median survival of 13, 13 and 3 months, respectively ( P  = 0.007). Change in Ki67 was also associated with median survival, with <50% reduction median survival 3 months, 50–80% median survival 7 months and >80% reduction median survival 13 months, P  = 0.02. Widespread treatment-related necrosis improved outcome, with >80% necrosis having a median survival of 13 months versus 3 months in those with <80% necrosis ( P  = 0.003). Conclusion: The presence of residual tumour at repeat craniotomy within 6 months of radiotherapy is not an independent indicator of prognosis. Patients with residual tumour that had a low Ki67 had a similar median survival as those with only treatment necrosis. Reduced proliferation of residual tumour cells and widespread necrosis may be more important indicators for future outcome. Highlights: Pathological features differentiating between pseudoprogression and true tumour progression. The role of proliferation index Ki67 as a possible biomarker for pseudoprogression. The presence of residual tumour cells at repeat craniotomy for high-grade glioma does not necessarily predict poor survival.